2022
DOI: 10.1039/d1ta09791a
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hierarchical MoO2/MoC@NC-CC free-standing anode applied in microbial fuel cells

Abstract: In general, more exoelectrogens’ enrichment implies higher power density. However, due to the low electrocatalytic activity of the anode, it limits the performance of microbial fuel cell. Here, based on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…As a result, tremendous efforts have been made to modify carbonaceous supports by ammonia treatment or coating with polymer or metal-based nanomaterials, and researchers found that the above-mentioned properties were improved to some extent . Recent work found that Fe-, Co-, Mn-, Ti-, or Mo-based nanomaterials displayed the ability to enhance the physicochemical and electrochemical properties of anodes for favorable bacterial attachment and fast EET rate. , For instance, branched-lily-like architecture of MoO 2 /MoC@NC was grown on carbon cloth, which substantially enriched Geobacter and displayed the power density of 2.93 W m –2 . Ti 3 C 2 MXene-modified carbon cloth as MFC anode generated a Coulombic efficiency of 23% due to the multilayer structure, high surface area, and excellent conductivity of MXene .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, tremendous efforts have been made to modify carbonaceous supports by ammonia treatment or coating with polymer or metal-based nanomaterials, and researchers found that the above-mentioned properties were improved to some extent . Recent work found that Fe-, Co-, Mn-, Ti-, or Mo-based nanomaterials displayed the ability to enhance the physicochemical and electrochemical properties of anodes for favorable bacterial attachment and fast EET rate. , For instance, branched-lily-like architecture of MoO 2 /MoC@NC was grown on carbon cloth, which substantially enriched Geobacter and displayed the power density of 2.93 W m –2 . Ti 3 C 2 MXene-modified carbon cloth as MFC anode generated a Coulombic efficiency of 23% due to the multilayer structure, high surface area, and excellent conductivity of MXene .…”
Section: Introductionmentioning
confidence: 99%
“…17 MoO 2 /MoC@NC was grown on carbon cloth, which substantially enriched Geobacter and displayed the power density of 2.93 W m −2 . 24 Ti 3 C 2 MXene-modified carbon cloth as MFC anode generated a Coulombic efficiency of 23% due to the multilayer structure, high surface area, and excellent conductivity of MXene. 25 In particular, Fe-and Co-based transition metal oxides, such as Fe 3 O 4 , 26 Fe 2 O 3 , 27 Co 2 O 3 , 28 and so on, have received profound attention as anodes because of their low price and high abundance, as well as excellent redox activities.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical performance was also assessed by electrochemical impedance spectroscopy (EIS), which was utilized to describe the resistance of charge transfer (R ct ) for the H-USH solution with or without H 2 S. The highfrequency semicircle in the EIS results was R ct between the electrolyte and the electrode, while the high-frequency straight line was the Ohm resistance (R ohm ). 48 As indicated in Figure 2g, the value of R ct of the H-USH solution decreased dramatically from 3.6 × 10 5 to 0.5 × 10 5 Ω after reacting with H 2 S, which showed a better charge transfer efficiency for the system after the reaction. Herein, H-USH could be used as an electrochemical sensor of H 2 S. Furthermore, the ultraviolet−visible (UV−vis) absorption spectra showed that CuS had a wide absorption region around 600−900 nm and an obvious strong absorbance peak at 800 nm compared with that of SiO 2 , H-UCNPs, and H-USH without H 2 S (Figures 2h and S11).…”
Section: ■ Results and Discussionmentioning
confidence: 80%
“…Due to the sensitivity and repeatability of the square-wave voltammetry (SWV) spectrum, it was generally used as the electronic signal for H 2 S sensing. , In Figure f, a stable current peak was found for the H-USH solution without any treatment. The electrochemical performance was also assessed by electrochemical impedance spectroscopy (EIS), which was utilized to describe the resistance of charge transfer ( R ct ) for the H-USH solution with or without H 2 S. The high-frequency semicircle in the EIS results was R ct between the electrolyte and the electrode, while the high-frequency straight line was the Ohm resistance ( R ohm ) . As indicated in Figure g, the value of R ct of the H-USH solution decreased dramatically from 3.6 × 10 5 to 0.5 × 10 5 Ω after reacting with H 2 S, which showed a better charge transfer efficiency for the system after the reaction.…”
Section: Resultsmentioning
confidence: 99%